Patient Safety Applications for Improving Health Care Quality - Rosyidah Rosyidah; Septian Emma Dwi Jatmika (Intelektual Pustaka Media Utama, 2015)
Patient safety is the fundamental thing that needs to be taken care of by medical staff when giving healthcare to patient especially in the Emergency Installation. PKU Muhammadiyah Public Hospital at Bantul has implemented Patient safety well in providing services for patients. Expected to be a reference for other hospitals to implement Patient safety as well as efforts to improve the quality of health services, but do not close the possibility there were still some deficiencies that could be made a suggestion for the PKU Muhammadiyah Bantul Hospital. There for researchers interested to review more detail how application of Patient safetyin Emergency Installation PKU Muhammadiyah Bantul Public Hospital in 2014. This research was qualitative observational study, using research subjects: The Head of the medical service, 1 Officer of Emergency Installation, the head of disaster management, 1 medical doctor, 1 nurse, and 4 patients that were taken with inclusion criteria: getting inpatient class III Hospitals in Yogyakarta, have inpatient more than 1 day. All the input items on the application of patient safety which include facilities, equipment, drugs, procedures, and activities of officers at Emergency Installation at PKU Muhammadiyah Bantul Hospital, as well as the application process is in compliance with the Guidelines of Observation Guidelines Patient Safety 2008 Survey and Guidelines for Accreditation of Hospital Emergency Services Specific Guidelines (revised edition 2007), ACT No. 44 Hospital in 2009, and patient safety procedures 2008. Patient perceived output includes five dimensions of quality (Tangible, Reliable, Responsiveness, Assurance and Empathy) all have the same perception of good and satisfying. Application on standard input, process and output is suit with Observation Guidelines for Patient Safety 2008 Survey and Guidelines for Accreditation of Hospital Emergency Services Specific Guidelines (revised edition 2007), ACT No. 44 Hospital in 2009, and patient safety procedures 2008.